THE DEATH PENALTY IN THE PUNISHMENT SYSTEM OF TRADITIONAL KAZAKH LAW (Journal of actual problems of jurisprudence, 2020)
The article is devoted to the study and analysis of the institution of the death penalty in the traditionallaw of the Kazakhs. The traditional law of Kazakhs was formed under the influence of nomadiclifestyle and political and legal structure.The criminal law of the traditional nomadic society of Kazakhs is characterized by the presence of twobasic principles. This is the principle of collective tribal responsibility and the principle of composition.Bythe period of the accession of Kazakhstan to Russia in the Kazakh customary law, there was thefollowing system of punishments: death penalty, corporal punishment, shameful punishment, extraditionof the guilty party of the victim, expulsion from the tribal community, Kun, Aip.Analysis of customary law shows that the death penalty under Kazakh customary law was appliedvery rarely and only with the consent of the Kurultai-people’s Assembly. This rule lasted until the 18thcentury.Starting from the second half of the 18th century, khans and sultans in Kazakh society began to usethe death penalty more often, both against their political opponents and those who stubbornly disobeythem.The analysis of historical and legal literature shows that in the traditional legal systems of CentralAsia and Kazakhstan there were many types of capital punishment.Key words: right, society, tradition, kun, ayip, death penalty.